Alimentación del recien nacido pre término y estado nutricional servicio de neonatología Hospital Belen de Trujillo - Cabrera Diaz, Yessenia Soledad (2015)
The research is descriptive correlational and cross-sectional, it was performed in order to determine the relationship between the type of preterm hospitalized infant feeding and nutritional status in the neonatology service of Belen Hospital in Trujillo. For data collection, three instruments were used: Type recording sheet feeding and nutritional status in newly born preterm (FRTAENRNPT), intrauterine growth curve for male Fenton 2013 (CCIUFRNPTM), intrauterine growth Fenton 2013 for females (CCIUFRNPTF). The results were tabulated and presented in statistical tables of single and double entry with number and percentage frequencies. For the analysis, the test of independence of criteria or Chi square (X2) was applied. The conclusion found was that 36.4 percent of the preterm infants were fed with fortified human milk; 32.7 percent was fed with special milk formula for premature; while 30.9 percent were fed exclusively with human milk. Related to nutritional status, 70.9 percent were appropriate for gestational age, 25.5 percent were small for gestational age, and 3.6 percent were large for gestational age. There is no significant relationship between the type of food and the nutritional status (p> 0.131)